Comparison and Correlation Between Students' Cognitive Competency in Regular Physics and Teaching and Learning Course - Sarkity, Dios; Pratama, Yudi (Jurnal Ilmiah Profesi Pendidikan, 2024)
Students learn exact and non-exact subjects in the biology education department. Lectures are required to be carried out using the case method. This research aims to determine differences in students' cognitive competence through the implementation of the case method in General Physics and Teaching and Learning courses and to determine the relationship between students' cognitive competence in General Physics and Teaching and Learning courses. This research is a correlational descriptive study carried out in June-July 2023. This research involved 32 biology education students as the research sample. Research data was collected using tests. Data were analyzed descriptively and using Spearman Rank. The results show that students' cognitive competence in the Teaching and Learning course is higher than in General Physics course. This is due to differences in the level of difficulty in studying lecture material. The research results also show a strong positive correlation between students' cognitive competence in exact courses (General Physics) and non-exact courses (Teaching and Learning). Further research is still needed to find other variables that can explain the relationship between these two variables because students' cognitive competence in exact courses cannot fully be used to indicate students' cognitive competence in non-exact courses.